2012
DOI: 10.1371/journal.pone.0051676
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Signatures Stabilizing the NAD(P)-Binding Rossmann Fold: A Structure Network Approach

Abstract: The fidelity of the folding pathways being encoded in the amino acid sequence is met with challenge in instances where proteins with no sequence homology, performing different functions and no apparent evolutionary linkage, adopt a similar fold. The problem stated otherwise is that a limited fold space is available to a repertoire of diverse sequences. The key question is what factors lead to the formation of a fold from diverse sequences. Here, with the NAD(P)-binding Rossmann fold domains as a case study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
(61 reference statements)
4
22
0
Order By: Relevance
“…9). It was reported that the glycine or alanine residues of the GXXXG/A motif form van der Waals interactions with either a valine or isoleucine residue located either seven or eight residues further back along the polypeptide chain and such motif holds together the secondary structures in core protein (Kleiger and Eisenberg, 2002;Bhattacharyya et al, 2012). Therefore, V/IXGX (1-2) GXXGXXXG/A is more strongly indicative than previously described motif (GX (1-2) GXXG), (Kleiger and Eisenberg, 2002).…”
Section: Predicted 3d Structures and Binding Sitesmentioning
confidence: 90%
See 1 more Smart Citation
“…9). It was reported that the glycine or alanine residues of the GXXXG/A motif form van der Waals interactions with either a valine or isoleucine residue located either seven or eight residues further back along the polypeptide chain and such motif holds together the secondary structures in core protein (Kleiger and Eisenberg, 2002;Bhattacharyya et al, 2012). Therefore, V/IXGX (1-2) GXXGXXXG/A is more strongly indicative than previously described motif (GX (1-2) GXXG), (Kleiger and Eisenberg, 2002).…”
Section: Predicted 3d Structures and Binding Sitesmentioning
confidence: 90%
“…Meanwhile, lycopene cyclase domain is related to FAD/ NADP(H) binding Rossmann fold domain superfamily. Rossmann folds can often be identified by GX (1-2) GXXG Motif (Kleiger and Eisenberg, 2002;Bhattacharyya et al, 2012). It was proposed that the first glycine provides a tight turn of the main-chain from the b-strand into the loop, and the second glycine allows close contact of the main-chain to the pyrophosphate of the nucleotide (Wierenga et al, 1986;Kleiger and Eisenberg, 2002).…”
Section: Predicted 3d Structures and Binding Sitesmentioning
confidence: 99%
“…Protein sidechain networks (PScN) are constructed by considering amino acid residues as nodes and edges are constructed between the nodes on the basis of noncovalent interactions between them (as evaluated from the normalized number of contacts between them) for each system. The details of the construction of such a graph at a particular interaction cut‐off ( I min ) and the implications of such graphs have been previously described . The noncovalent interaction between side chain atoms of amino acid residues (with the exception of Gly where Cα atom) are considered, ignoring the interaction between sequence neighbors (±2 immediate neighbors).…”
Section: Methodsmentioning
confidence: 99%
“…The interactions in PScN representation can be quantified by considering the residue connections ranging from atom–atom contact to highly packed interactions like aromatic stacking . Herein, this representation enables the construction of networks based on weak and strong noncovalent interactions at the sidechain level and this unique approach has been proven to provide valuable biological insights …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation